Primary culture and endocrine functional analysis of Leydig cells in ducks (Anas platyrhynchos) - Chu, Xiaoya; Javed, Aiman; Ashraf, Muhammad Faizan; Gao, Xiuge; Jiang, Shanxiang (Frontiers in Endocrinology, 2023)
Testicular Leydig cells (LCs) are the primary known source of testosterone, which is necessary for maintaining spermatogenesis and male fertility. However, the isolation, identification, and functional analysis of testosterone in duck LC is still ambiguous. The aim of the present study was to establish a feasible method for isolating highly purified primary duck LCs. The highly purified primary duck LCs were isolated from fresh testis of 2-month-old duck via the digestion of collagenase IV and Percoll density gradient centrifugation and the hematoxylin-eosin (HE), immunohistochemistry (IHC) staining, ELISA and Radio immunosorbent Assay were performed. Results revealed that the LCs were prominently noticeable in the testicular interstitium of 2-month-old duck as compared to other stages (6-month and 1year-old). Furthermore, IHC demonstrated that the cultured LC occupied 90% area of the petri dish and highly expressed 3β-HSD after 24 hours after culture (hac) as compared to 48 hac and 72 hac. Additionally, ELISA and Radio Immunosorbent Assay indicates that the testosterone level in cellular supernatant was highly expressed in 24 hac and 48 hac, whereas gradually decreased in 72 hac and 96 hac, indicating the primary duck LCs secrete testosterone at early stage. Based on the above results, the present study has effectively developed a technique for isolating highly purified primary duck LC and identified its biological function in synthesize testosterone.